Konflik Sosial Suku Anak Dalam (Orang Rimba) di Provinsi Jambi - Wandi Wandi (SIMULACRA: JURNAL SOSIOLOGI, 2019)
This article aims to explore the social conflicts in the utilization of natural resources of the Anak Dalam or Orang Rimba tribes. The purpose of this study is to find out the cause of social conflict that occurred. The research method used is a qualitative method based on literature studies and interviews as well as the accumulation of understanding from various primary studies conducted on the Suku Anak Dalam or Orang Rimba community. The results of this study are, first, there are differences in perceptions regarding regional claims between the state, companies, surrounding villagers, as well as Suku Anak Dalam or Orang Rimba. Secondly, there is a conflict of interest in the utilization of forest resources that were previously home to the Anak Dalam or Orang Rimba tribes. Third, there is competition in the use of forest resources. Fourth, it is a dilemma for Suku Anak Dalam or Orang Rimba in the midst of the development of the times, where they have lived for a long time, and have collided with policies that are oriented towards group interests. This study is expected to be able to provide an overview of the conflicts and to provide solutions to the rights and survival of the Suku Anak Dalam or Orang Rimba communities.